EFIKASI DIRI SEBAGAI INTERNAL BUFFER TERHADAP BURNOUT - Lailani, Fereshti (Universitas Sahid Surakarta, 2015)
ABSTRACTBurnoutÂ isÂ aÂ psychologicalÂ responseÂ toÂ workÂ stressÂ thatÂ isÂ characterizedÂ by emotionalÂ exhaustion,Â depersonalization,Â andÂ reducedÂ feelingÂ ofÂ personal accomplishment (low personal accomplishment). This paper intends to explain one of the variables that the results of some studies have shown to have a role in burnout , which is selfÂ âÂ efficacy.Â Self-efficacy is the beliefs about oneâs ability to accomplish specific tasks. Self-efficacyÂ affectsÂ employeesâÂ levelÂ toÂ effortÂ andÂ persistenceÂ whenÂ learningÂ difficult tasks.Â AÂ numberÂ ofÂ researchÂ studyÂ wasÂ foundÂ thatÂ perceivedÂ senseÂ ofÂ self-efficacyÂ was correlatedÂ withÂ perceivedÂ burnoutÂ :Â theÂ lowerÂ theÂ senseÂ ofÂ self-efficacyÂ moreÂ was perceived burnout. The individuals having low self-efficacy have not much control of their behavior and actions. They are more vulnerable to burnout.Key words :Burnout, Self-Efficacy